2016
DOI: 10.4238/gmr.15038685
|View full text |Cite
|
Sign up to set email alerts
|

Combining abilities for agronomic traits and marker-assisted selection for Potato virus X and Potato virus Y resistance

Abstract: ABSTRACT. Disease-resistant potato cultivars with good tuber appearance and desirable agronomic traits are essential for meeting the demands of producers and the market. Attaining these cultivars is the focus of potato breeding programs whose aim is to benefit the productive chain. The purpose of this study was to estimate combining abilities and evaluate potato clones based on tuber appearance, yield, and resistance to the PVY and PVX viruses. Crosses between four commercial cultivars of potato with good tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…In addition the baker's ratio for dry matter content was 0.58, signifying the predominance of additive genetic effects in controlling dry matter content. The predominance of additive gene action for dry matter content has also been reported by other studies [18,28]. These studies reported GCA effects being greater than SCA effects for dry matter content.…”
Section: Discussionsupporting
confidence: 82%
“…In addition the baker's ratio for dry matter content was 0.58, signifying the predominance of additive genetic effects in controlling dry matter content. The predominance of additive gene action for dry matter content has also been reported by other studies [18,28]. These studies reported GCA effects being greater than SCA effects for dry matter content.…”
Section: Discussionsupporting
confidence: 82%
“…Os caracteres apontamento, textura da periderme, profundidade de olhos, e peso específico dos tubérculos apresentaram predominância dos efeitos da CGC, em ambas as gerações (Tabela 2). Guedes et al (2016) também relatou predomínio da CGC para textura da periderme, profundidade de olhos, e peso específico dos tubérculos. Terres et al (2017) trabalhando com caracteres de aparência e de produtividade de tubérculos também observaram efeitos aditivos para apontamento.…”
Section: Resultsunclassified
“…Existem na literatura alguns trabalhos relacionados a seleção de genitores para caracteres de aparência (TERRES et al, 2017;GUEDES et al, 2016;SILVA et al, 2013;KUMAR et al, 2008;NEELE et al, 1991), entretanto são poucos trabalhos são encontrados na literatura para seleção de genitores para tolerância ao calor (MENEZES et al, 2001). Assim o objetivo deste trabalho foi estimar as capacidades de combinação e identificar genitores que agreguem tolerância ao calor, e também a boa aparência de tubérculos.…”
Section: Introductionunclassified
“…The aim of this study was to assess the adaptability and stability of advanced clones from the potato breeding program (PROBATATA) that are resistant to the PVY, through use of the GGE biplot method. Guedes et al (2016) selected 18 clones with good tuber appearance that carried the allele Ry adg , which confers extreme resistance to PVY. These 18 clones, named MLG, and four check cultivars commonly cultivated in the state of Minas Gerais (Agata, Cupido, Asterix, and Atlantic) were used to perform this study.…”
Section: Mhml Andrade Et Almentioning
confidence: 99%